Mechanisms and Emerging Therapies in Tremor Disorders - Grimaldi, Giuliana; Manto, Mario; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Tremor is intimately linked to the numerous interactions of the central and peripheral nervous system components tuning motor control, from the cerebral cortex up to the peripheral effectors. Activities of central generators, reflex loop delays, inertia, stiffness and damping are all factors influencing features of tremor. This book discusses the pathophysiology of tremor including membrane mechanisms and rodent models, the advances in genetics and the musculoskeletal models pertinent to body oscillations. The main forms of tremor encountered during clinical practice are considered, taking into account neuroimaging aspects. The book covers recent advances in methodologies and techniques of assessment, and provides practical informations for the daily management. In addition to pharmacological treatments, neurosurgical approaches such as deep brain stimulation (DBS) and thalamotomy are discussed. Emerging techniques under development are also introduced. Future challenges are also presented.
Part 1: Fundamental aspects -- Definition of tremor -- Membrane mechanisms of tremor -- Rodent models of tremor -- Advances in genetics of human tremor -- Musculo-skeletal models of tremor -- Part 2: The various forms of tremor in clinical practice: presentation and mechanism -- Physiological tremor -- Rest tremor -- Postural tremors -- Isometric tremor -- Essential Tremor and Other Forms of Kinetic Tremor -- Dystonic tremor -- Orthostatic tremor -- Vocal tremor -- Update in Familial Cortical Myoclonic tremor with Epilepsy (FCMTE) -- Post-traumatic tremor and Other Post-Traumatic Movement Disorders -- Psychogenic tremor -- Tremor in childhood -- Part 3: Assessment of tremor: clinical, neurophysiological and neuroimaging aspects -- Assessment of tremor: clinical and functional scales -- Instrumentation: classical and emerging techniques -- Signal processing -- Diffusion imaging in tremor -- The metabolic networks in Parkinson's disease -- Part 4: Therapies of tremor -- Pharmacological treatments of tremor -- Thalamotomy -- Brain Stimulation -- Dopaminergic Influences on Rest and Action Tremors and Emerging Therapies for Tremor.
Keywords: Medicine; Neurology; Biomedicine; Biomedicine general; Neurology